Determinan Efektivitas Pelaporan Keuangan Survei UKM di Kabupaten Boyolali - Aprilia Dista; Aris Eddy Sarwono (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Difficulties in preparing proper financial reports remain a common issue among small and medium enterprises (SMEs), particularly in producing information that is accurate and useful for decision-making. This condition highlights the importance of determining the main factors that contribute to enhancing the effecttiveness of financial reporting practices. This study examines the role of financial literacy, the use of accounting information systems, and training in enhancing the effectiveness of financial reporting among SMEs. A quantitative approach was applied using survey data collected from 100 SME actors in Boyolali Regency, selected based on specific criteria. The data were analyzed using multiple linear regression after passing instrument testing and classical assumption procedures. The findings reveal that financial literacy, the utilization of accounting information systems, and training each contribute positively to the effectiveness of financial reporting. Furthermore, these variables collectively explain a substantial portion of the variation in reporting quality. The findings suggest that strengthening financial knowledge, encouraging the adoption of accounting technology, and providing continuous training are essential steps in improving financial reporting practices among SMEs.